Test-retest reliability and clinical correlates of the Eurofit test battery in people with alcohol use disorders. (January 2019) - Vancampfort, Davy; Hallgren, Mats; Vandael, Hannelore; Probst, Michel; Stubbs, Brendon; Raymaekers, Simon; Van Damme, Tine
Highlights: The Eurofit is a reliable fitness test in people with alcohol use disorders. The Eurofit is a feasible fitness test in people with alcohol use disorders. Those with a longer illness duration perform worse on the Eurofit. Those who are less physically active perform worse on the Eurofit. Abstract: People with alcohol use disorder (AUD) are at an increased risk for cardiovascular diseases (CVD). Physical fitness is a predictor of CVD and premature mortality. Currently, no existing measures of physical fitness used in the general population have been tested for validity and reliability in this vulnerable population. Therefore, we examined the reproducibility, feasibility and correlates of the Eurofit test battery in this population. From 32 men (age = 40.8 ± 13.8years; illness duration = 10.2 ± 10.3years; body mass index, BMI = 24.8 ± 3.8) and 13 women (age = 41.9 ± 12.1years; illness duration = 13.7 ± 13.1years; BMI = 26.3 ± 4.9) with AUD two trials of the Eurofit test, administered within one week, were analyzed. All patients also completed the International Physical Activity Questionnaire, the Positive Affect and Negative Affect Scale and Alcohol Use Disorders Identification Test. All Eurofit items showed good reproducibility with intraclass correlation coefficients ranging from 0.82 for the flamingo balance test to 0.97 for the standing broad jump and handgrip strength tests. Better performance on Eurofit test items was associated with younger age, a shorter illness duration, a lower BMI and higher physical activity levels. The current study demonstrates that the Eurofit test can be recommended as a reliable test for evaluating the physical fitness of inpatients with alcohol use disorder.